Analisis Debit Banjir Metode Hidrograf Satuan Sintetis (HSS) Nakayasu dan Synder pada Krueng Sabee Aceh Jaya - Muhammad Ridha; Amalia; Muhammad Zardi; Tety Sriana; Mery Silviana; Meliyana; Susi Sakia (Universitas Iskandar Muda, 2025)
Krueng Sabee is one of the rivers located in Krueng Sabee District, Aceh Jaya Regency. Krueng Sabee has a main river with a length of 33.27 km and a watershed area of 380.90 km2 and an average river elevation of 0.4%. Krueng Rusi and Krueng Cangeh divide the Krueng Sabee River flow in the upstream. Krueng Sabee often overflows which causes flooding around its flow area. To determine the design flood discharge for the Return Period (PU) of 2.5, 10, 25, 50 and 100 years that occurred in Krueng Sabe using the HSS Nakayasu and HSS Synder Methods is the main objective of this study. Rainfall data used from station A in Pulo Raya Village and station B in Pante Kuyun Village. The flood discharge for Return Period (PU) 2, 5, 10, 25, 50, and 100 is 1716.66 m³/sec, 1985.10 m³/sec, 2162.83 m³/sec, 2387.39 m³/sec, 2553.99 m³/sec and 2719.36 m³/sec is the result of the Nakayasu HSS Method analysis. The Snyder HSS method, obtains the design flood discharge values for various Return Periods (PU) as follows: 2 years 14,479.83 m³/s, 5 years 16,746.64 m³/s, 10 years 18,247.47 m³/s, 25 years 20,143.77 m³/s, 50 years, 21,550.55 m³/s Return Period 100 years 22,946.95 m³/s. It was found that the Snyder Synthetic Unit Hydrograph (HSS) method produces a larger flood discharge compared to the Nakayasu HSS.